The impact of globalization on higher education in Kazakhstan: political and legal aspects (Journal of actual problems of jurisprudence, 2021)
The impact of globalization on higher education in Kazakhstan: political and legal aspects The purpose of this paper is to carry out a theoretical and historical analysis of political and legal acts of internationalization and to identify the impact of globalization processes on higher education in certain countries. The research is conducted by documentary analysis based on the qualitative research method. The origins of global trends in higher education, such as the Washington Consensus, the Bologna Process, and other political phenomena, have been explored through documentary analysis of legal acts. Additional materials for research were obtained from various official documents and information sources using the method of secondary data analysis. Also, research papers on this topic were analysed using the methods of historical and logical analysis. As a result of the study, it was revealed that global policy in the field of higher education is based on a neoliberal idea and was initiated by Western countries. It was noted that the Washington Consensus and some international financial institutions were involved in the dissemination of neoliberal ideas in higher education. It was concluded that the idea of solving social issues in higher education through the market model was developed on the advice of American economists and was aimed at establishing American economic dominance. It has been suggested that the effective functioning of the governance system is a key factor affecting the overall efficiency of the university, and in this regard, Kazakhstani universities still need to be improved. It is hoped that the recommendations and conclusions of the study will be taken into account  by the authorities when reforming the governance system in higher education. It is also expected that this article will serve as a theoretical underpinning for future research on this topic. Key words: globalization, neoliberalism, state universities, governance, law and politics.